Hollow sea urchin carbon based on concentrated gel carbonization as well as preparation method and application of hollow sea urchin carbon
Through the preparation method of hollow sea urchin carbon based on concentrated glue carbonization, the problems of low capacity and poor rate performance of existing capacitive carbon materials are solved, and the orderly preparation of hollow sea urchin carbon structure is realized, with optimized high rate performance and suitable for super The electrode material of the capacitor.
Patent Information
- Application Number
- CN202411574375.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
AI Technical Summary
Existing capacitive carbon materials have problems with low capacity and poor rate performance in commercial applications, and the structure of ordered hierarchical porous structures requires expensive chemical vapor deposition or complex stenciling methods, which cannot achieve large-scale commercial preparation.
Using the method of preparing hollow sea urchin carbon based on concentrated gel carbonization, the concentrated gel is prepared by dissolving zinc salt, ammonium fluoride and polyvinylpyrrolidone in a polar solvent, stirring at room temperature and distilling under reduced pressure, and carbonizing under inert conditions. The orderly hollow sea urchin carbon structure is produced.
This method is simple and fast, suitable for large-scale commercial preparation. The prepared hollow sea urchin carbon has optimized high-rate performance and is suitable for electrode materials of supercapacitors. It can effectively permeate the electrolyte under high load conditions and significantly improve the performance of the capacitor.
Smart Images

Figure CN119409168A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to hollow sea urchin carbon and a preparation method and application thereof, and relates to hollow sea urchin carbon based on concentrated gum carbonization and a preparation method and application thereof. Background Art
[0002] The continuous consumption of fossil energy worldwide has led to the greenhouse effect and increasing extreme weather, and has also caused serious environmental pollution. Advanced clean energy, such as solar energy, wind energy, geothermal energy or tidal energy, is a potential energy alternative. However, their intermittent nature, regionality and uneven temporal and spatial distribution have severely limited their large-scale application. Therefore, it is urgent to develop advanced and efficient energy storage technology.
[0003] Among many energy storage technologies, supercapacitors are ideal energy storage technologies due to their technical advantages such as high power density, ultra-long cycle stability, and high safety. Among them, electrochemical double-layer supercapacitors represented by porous carbon materials have the advantages of abundant sources, simple processing, diverse preparation methods, excellent rate performance, and high safety. However, the current capacitor carbon materials for commercial applications (such as YP50F from Kuraray Company, Japan) are generally prepared by carbonization of carbon-containing precursors (such as biomass, asphalt, coal, etc.) under an inert gas atmosphere, lacking effective hierarchical porous structure regulation, resulting in low capacity and poor rate performance. Carbon materials with ordered hierarchical porous structures effectively reduce the ion diffusion distance due to the three-dimensional conductive paths formed by themselves and the effective penetration of electrolytes, showing improved rate performance compared to traditional commercial activated carbon. However, the construction of ordered hierarchical porous structures generally requires the use of expensive chemical vapor deposition (CVD) or complex template methods, which cannot be achieved for large-scale commercial preparation, so it is necessary to develop simple and effective preparation strategies. Summary of the invention
[0004] Technical issues to be solved
[0005] In order to avoid the shortcomings of the prior art, the present invention proposes a hollow sea urchin carbon based on concentrated gel carbonization and its preparation method and application. The purpose is to develop a simple and effective ordered hollow sea urchin carbon for high-rate supercapacitors. Its characteristics are: based on the zinc salt concentrated gel carbonization strategy, the zinc salt conversion and the polymer precursor carbonization are carried out simultaneously to prepare an ordered hollow sea urchin carbon structure. The ordered hollow sea urchin carbon structure is further processed into an electrode sheet for supercapacitors, which has optimized high-rate performance. This preparation method is convenient, fast, low-cost, and suitable for popularization and application.
[0006] Technical Solution
[0007] A method for preparing hollow sea urchin carbon based on concentrated rubber carbonization, characterized by the following steps:
[0008] Dissolve zinc salt, ammonium fluoride NH4F and polyvinylpyrrolidone PVP in a polar solvent; stir at room temperature to obtain a uniform colloid;
[0009] The jelly is distilled under reduced pressure to recover the solvent to obtain a concentrated gel;
[0010] The obtained concentrated gel is carbonized under inert conditions to obtain hollow sea urchin carbon based on concentrated gel carbonization with a spatial hierarchical structure.
[0011] The dosage ratio of the zinc salt, ammonium fluoride NH4F and polyvinyl pyrrolidone PVP is 0-50 mmol; 0-100 mmol; 0.5-10 g.
[0012] The amount of the polar solvent used during the dissolution is 10 to 50 ml.
[0013] The zinc salt is zinc nitrate, zinc chloride, zinc sulfate or zinc acetate.
[0014] The polyvinyl pyrrolidone is polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K90 or polyvinyl pyrrolidone K88-96.
[0015] The polar solvent is N,N-dimethylformamide DMF or N,N-dimethylacetamide.
[0016] The mixture was stirred at room temperature for more than 6 hours.
[0017] The carbonization is carried out in a tubular furnace at a temperature ranging from 500 to 1000° C., and the inert gas introduced is nitrogen or argon.
[0018] A hollow sea urchin carbon based on concentrated gum carbonization prepared by the method is characterized in that: zinc salt conversion and polymer precursor carbonization are carried out simultaneously, relying on the intrinsic zinc salt conversion and polymer carbonization to obtain an ordered hierarchical carbon structure, presenting a sea urchin-like structure with uniform morphology; the hollow sea urchin carbon has open spaces between particles, and the secondary branched structures of the sea urchin carbon are interspersed with each other.
[0019] A hollow sea urchin carbon based on concentrated gel carbonization is characterized in that the ordered hierarchical carbon structure is further processed into an electrode sheet for supercapacitors.
[0020] Beneficial Effects
[0021] The present invention proposes a hollow sea urchin carbon based on concentrated gel carbonization and its preparation method and application. Based on the zinc salt concentrated gel carbonization strategy, the zinc salt conversion and the polymer precursor carbonization are carried out simultaneously to prepare an ordered hollow sea urchin carbon structure. The ordered hollow sea urchin carbon structure is further processed into an electrode sheet for supercapacitors, which has optimized high-rate performance. The preparation method is convenient, fast, low-cost, and suitable for popularization and application. The method of the present invention is convenient and fast, does not require a complex synthesis process, and does not require expensive instruments and equipment; the prepared hollow sea urchin carbon structure is evenly dispersed, which is conducive to the effective penetration of the electrolyte under high load conditions; the intrinsic zinc salt conversion contributes to the formation of a spatial multi-level structure, without the need for additional complex activation steps; after being assembled into an electrode material, it exhibits high-rate performance; thanks to the flexibility and processability of the concentrated gel, the method has a wide range of applications and can be used to customize patterns. The present invention has a high reference value for the development of uniform, high-rate capacitor carbon materials with a spatial structure, and is suitable for popularization and application.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] 1. The concentrated gel required by the present invention is simple to prepare and can be carried out in an open environment at room temperature without complicated chemical and physical synthesis, and is suitable for large-scale commercial preparation in different regional environments.
[0024] 2. The preparation process of hollow sea urchin carbon is simple and does not require expensive and complex equipment. It relies on the internal zinc salt conversion and polymer carbonization to present a uniform sea urchin shape. It can be stored for a long time in air at room temperature. It has a hollow structure and is suitable for a variety of chemical and physical application environments.
[0025] 3. The hollow sea urchin carbon of the present invention has open spaces between particles, and the secondary branched structures of the sea urchin carbon are interspersed with each other, which is conducive to forming a stable conductive network, accelerating electrolyte penetration and shortening the electron transmission distance, and has optimized rate performance.
[0026] 4. The precursor of the concentrated gel is highly flexible and processable, and can be used to construct integrated electrodes with customized patterns. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an electronic photograph of the concentrated gel prepared in Example 1;
[0028] Figure 2 This is a scanning electron microscope image of the uniformly dispersed hollow sea urchin carbon prepared in Example 1. The size of the hollow sea urchin carbon reaches several microns, showing a secondary branched structure extending to the surroundings. The branched structures are interspersed and connected with each other to form a conductive network, which is beneficial to enhancing the overall conductivity of the material. There are more spaces between the sea urchin carbons, which is beneficial to the transmission and rapid penetration of electrolyte ions, thereby increasing the effective interface contact between the electrolyte ions and the carbon surface.
[0029] Figure 3 This is the cyclic voltammetry test curve of the HCN-900 electrode material prepared in Example 1 in a three-electrode system (6M KOH electrolyte). The test voltage window is -1V to 0V, and the scan rate range is 100mV·s -1 ~1500mV·s -1 , the hollow sea urchin carbon electrode material can -1 It can still maintain a nearly rectangular shape at an ultra-high scan rate, demonstrating its ultra-fast ion transport kinetics and excellent rate performance. It only takes 0.07s to fully charge and can be used for high-rate energy storage.
[0030] Figure 4 This is an electron photograph of the integrated HCN-Ni-900 electrode prepared in Example 2.
[0031] Figure 5 This is the cyclic voltammetry test curve of the integrated HCN-Ni-900 electrode prepared in Example 2 in a three-electrode system (6M KOH electrolyte). The test voltage window is -1V to 0V, and the scan rate range is 2mV·s -1 ~1500mV·s -1 , HCN-Ni-900 electrode even at 1500mV·s -1 The nearly rectangular shape can be maintained even at high scan rates, demonstrating the ultrafast ion transport and excellent rate performance of the integrated electrode. DETAILED DESCRIPTION
[0032] The present invention will now be further described with reference to the embodiments and the accompanying drawings:
[0033] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0034] The zinc salt concentrated gel preparation method is as follows: zinc nitrate, ammonium fluoride (NH4F) and polyvinyl pyrrolidone (PVP) are dissolved in N,N-dimethylformamide (DMF), stirred at room temperature for more than 6 hours, and a uniform colloid is obtained. The colloid is distilled under reduced pressure to recover the solvent to obtain a concentrated gel. The obtained concentrated gel is carbonized under inert conditions to obtain a carbon material (HCN) with a spatial hierarchical structure.
[0035] Preferred is zinc nitrate (or zinc chloride, zinc sulfate, zinc acetate).
[0036] Preferred polyvinyl pyrrolidone K30 (or K90, K88-96).
[0037] The preferred polar solvent is N,N-dimethylformamide (or N,N-dimethylacetamide).
[0038] The preferred usage ratio of zinc nitrate, ammonium fluoride, polyvinyl pyrrolidone and N,N-dimethylformamide is 0-50 mmol; 0-100 mmol; 0.5-10 g; 10-50 ml.
[0039] Preferably, the carbonization is carried out in a tubular furnace at a temperature ranging from 500 to 1000° C. using inert gas nitrogen (or argon).
[0040] The present invention is further described below in conjunction with specific embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] Step (1) 5 mmol zinc nitrate, 5 mmol ammonium fluoride, and 2 g polyvinyl pyrrolidone were dissolved in 10 mL N,N-dimethylformamide and stirred at room temperature for 12 hours to obtain a colloid.
[0043] Step (2) distilling the colloid under reduced pressure at 65° C. for 2 hours, recovering the N,N-dimethylformamide solvent, and obtaining a precursor concentrated gel.
[0044] Step (3) The concentrated gel is placed in a tubular furnace, and carbonized at 900°C for 2 hours under nitrogen protection, with a heating rate of 2°C / min, and then naturally cooled to room temperature. Then, it is soaked in a 1 mol / L hydrochloric acid solution to remove residual zinc compounds. Then, it is repeatedly rinsed with water, placed in a vacuum oven to be fully dried, and stored for later use, i.e., HCN-900.
[0045] Step (4) Ultrasonic mixing of the HCN-900 sample, conductive carbon black and polytetrafluoroethylene in a ratio of 8:1:1, rolling into a thin sheet after drying, and pressing the thin sheet with the current collector into a sandwich structure electrode.
[0046] Example 2
[0047] Step (1) 5 mmol zinc nitrate, 5 mmol ammonium fluoride, and 2 g polyvinyl pyrrolidone were dissolved in 10 mL N,N-dimethylformamide (DMF) and stirred at room temperature for 12 hours to obtain a colloid.
[0048] Step (2) distill the colloid under reduced pressure at 65° C. for 2 hours, recover the N,N-dimethylformamide solvent, and obtain a precursor concentrated gel. Cut the concentrated gel into any shape, and press it onto the nickel foam with a pressure of 0.1 MPa to construct an initial integrated electrode.
[0049] Step (3) Place the initial integrated electrode in a tubular furnace, under nitrogen protection, carbonize at 900°C for 2 hours, with a heating rate of 2°C / min, and naturally cool to room temperature. Soak in 1 mol / L hydrochloric acid solution to remove residual zinc compounds. Rinse repeatedly with water, place in a vacuum oven to fully dry and store for later use, and obtain an integrated HCN-Ni-900 electrode.
[0050] Example 3
[0051] The difference between step (1) and Example 1 is that N,N-dimethylacetamide is used as the solvent.
[0052] Example 4
[0053] The difference between step (1) and Example 2 is that N,N-dimethylacetamide is used as the solvent.
[0054] Example 5
[0055] The difference between step (1) and Example 1 is that the carbonization is carried out at 800° C. in a tube furnace for 2 hours.
[0056] Example 6
[0057] The difference between step (1) and Example 2 is that the carbonization is carried out at 800° C. for 2 hours in a tube furnace.
[0058] Example 7
[0059] The difference between step (1) and Example 1 is that the carbonization is carried out at 1000° C. for 2 hours in a tube furnace.
[0060] Example 8
[0061] The difference between step (2) and Example 2 is that carbonization is performed at 1000° C. for 2 hours in a tubular furnace.
[0062] According to the diagrams of the above embodiments, the beneficial effects of the invention are further demonstrated:
[0063] Figure 2 This is a scanning electron microscope image of the uniformly dispersed hollow sea urchin carbon prepared in Example 1. The size of the hollow sea urchin carbon in the image reaches several microns, showing a secondary branched structure extending to the surroundings. The branched structures are interspersed and connected with each other to form a conductive network, which is beneficial to enhancing the overall conductivity of the material. There are more spaces between the sea urchin carbons, which is beneficial to the transmission and rapid penetration of electrolyte ions, thereby increasing the effective interface contact between the electrolyte ions and the carbon surface.
[0064] Figure 3 The cyclic voltammetry curve of the HCN-900 electrode material prepared in Example 1 in a three-electrode system (6M KOH electrolyte) is shown in the figure. The test voltage window is -1V to 0V, and the scan rate range is 100mV·s-1 ~1500mV·s -1 , the hollow sea urchin carbon electrode material can -1 It can still maintain a nearly rectangular shape at an ultra-high scan rate, demonstrating its ultra-fast ion transport kinetics and excellent rate performance. It only takes 0.07s to fully charge and can be used for high-rate energy storage.
[0065] Figure 4 This is an electronic photograph of the integrated HCN-Ni-900 electrode prepared in Example 2. Figure 5 This is the cyclic voltammetry test curve of the integrated HCN-Ni-900 electrode prepared in Example 2 in a three-electrode system (6M KOH electrolyte). The test voltage window is -1V to 0V, and the scan rate range is 2mV·s -1 ~1500mV·s -1 , HCN-Ni-900 electrode even at 1500mV·s -1 The nearly rectangular shape can be maintained even at high scan rates, demonstrating the ultrafast ion transport and excellent rate performance of the integrated electrode.
Claims
1. A method for preparing hollow sea urchin carbon based on concentrated rubber carbonization, characterized in that Here are the steps: Dissolve zinc salt, ammonium fluoride NH4F and polyvinylpyrrolidone PVP in a polar solvent; stir at room temperature to obtain a uniform colloid; The jelly is distilled under reduced pressure to recover the solvent to obtain a concentrated gel; The obtained concentrated gel is carbonized under inert conditions to obtain hollow sea urchin carbon based on concentrated gel carbonization with a spatial hierarchical structure.
2. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The zinc salt, ammonium fluoride NH4F and polyvinyl pyrrolidone PVP are used in a ratio of 0 to 50 mmol; 0 to 100 mmol; 0.5~10g。 3. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The amount of the polar solvent used during the dissolution is 10 to 50 ml.
4. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The zinc salt is zinc nitrate, zinc chloride, zinc sulfate or zinc acetate.
5. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The polyvinyl pyrrolidone is polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K90 or polyvinyl pyrrolidone K88-96.
6. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The polar solvent is N,N-dimethylformamide DMF or N,N-dimethylacetamide.
7. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The mixture was stirred at room temperature for more than 6 hours.
8. The method for preparing hollow sea urchin carbon based on concentrated rubber carbonization according to claim 1, characterized in that: The carbonization is carried out in a tubular furnace at a temperature ranging from 500 to 1000° C., and the inert gas introduced is nitrogen or argon.
9. A hollow sea urchin carbon based on concentrated rubber carbonization prepared by the method according to any one of claims 1 to 8, characterized in that: The zinc salt conversion and the polymer precursor carbonization are carried out simultaneously, and an ordered hierarchical carbon structure is obtained based on the internal zinc salt conversion and polymer carbonization, presenting a sea urchin-like structure with uniform morphology; the hollow sea urchin carbon has open spaces between particles, and the secondary branched structures of the sea urchin carbon are interspersed with each other.
10. A hollow sea urchin carbon based on concentrated rubber carbonization according to claim 9, characterized in that: The ordered hierarchical carbon structure is further processed into electrode sheets for supercapacitors.